Foreign ownership and the pursuit of global technological arbitrage opportunities; European Journal of International Management; Vol. XX, iss. X - Anokhin S. A. Sergey Aleksandrovich; Spitsin V. V. Vladislav Vladimirovich; Trifonov A. Yu. Andrey Yurievich; Antonova I. S. Irina Sergeevna (2021, 2021)
Title screen